ANALYSIS OF USER SATISFACTION WITH PARIAMAN PEOPLE'S MARKET ASSETS AND FACILITIES - Laura, Fedwina; Wardi, Wardi; Anif, Bahrul (Fakultas Teknik Universitas Muhammadiyah Sumatera Barat, 2025)
User satisfaction has an influence on customer retention, purchase intention and willingness to repeat business. Satisfied users tend to be loyal, while dissatisfied users tend to leave the transaction. The aim of the research is to analyze factors and determine the dominant factors in user satisfaction with Pariaman people's market facilities. Then look for solutions to increase user satisfaction at the Pariaman People's Market. The research method used was qualitative by interviewing informants. The results of the research found that the dominant factors in user satisfaction with the Pariaman People's Market facilities were: The condition and atmosphere of the market was not congested, all traders were of the opinion that the condition and atmosphere of the not congested market had not yet reached the level of user satisfaction with the Pariaman People's Market facilities